Attitude Towards Self-Realization Abroad of the Students from Different Ukrainian Regions - Blinova, Oksana Evgenivna (Psychological Prospects Journal, 2012)
The results of empirical investigation of migrational readiness of students from different Ukrainian universities, their attitude towards labour migration and self-realization abroad are presented in the article.